Influence of Infrastructure and Work Motivation on Teacher’s Performance in Patra Mandiri Palembang High School - Fitria, Eka; Fitria, Happy; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2023)
The three effects on teacher’s performance at SMA Patra Mandiri Palembang that this study seeks to identify and describe are: 1) the impact of school infrastructure; 2) the impact of work motivation; and 3) the combined impact of school infrastructure and work motivation. Teachers at SMA Patra Mandiri 1 and 2, SMA Fitra Abdi, comprising 86 teachers, comprised the population and sample in this study. Data gathering methods: 1) an interview; 2) an observation; and 3) documentation. Techniques for data analysis with the SPSS software package for Windows version 26: the tests for normality, linearity, multicollinearity, and heteroscedasticity. Simple linear regression, multiple linear regression, multiple correlation (R), determinant (R2), and the F test are all methods for testing hypotheses. The findings of this study show that in SMA Patra Mandiri Palembang, infrastructure, motivation to collaborate, and facilities have a significant and beneficial influence on teacher’s performance.